Women artists in the 20th and 21st century - Grosenick, Uta.; Becker, Ilka. (Koln Los Angeles Taschen, 2005)
It's a women's world (TASCHEN's 25th anniversary special edition) Many of the century's greatest artistic talents grace the pages of this tome, each artist represented by six pages of illustrations and photographs covering the various phases of her life and work, including biographical portraits and text.
Marina Abramovic -- Laurie Anderson -- Janine Antoni -- Vanessa Beecroft -- Louse Bourgeois -- Hanne Darboven -- Sonia Delaunay -- Rineke Dijkstra -- Tracy Emin -- Valie Export -- Sylvie Fleury -- Katharina Fritsch -- Ellen Gallagher -- Isa Genzken -- Nan Goldin -- Natalia Goncharova -- Barbara Hepworth -- Eva Hesse -- Hannah Hoch -- Candida Hofer -- Nancy Holt -- Jenny Holzer -- Rebecca Horn -- Magdalena Jetelova -- Frida Kahlo -- Toba Khedoori -- Lee Krasner -- Barbara Kruger -- Louise Lawler -- Tamara de Lempicka -- Sherrie Levine -- Agnes Martin -- Tracey Moffatt -- Mariko Mori -- Shirin Neshat -- Louise Nevelson -- Cady Noland -- Georgia O'Keeffe -- Yoko Ono -- Meret Oppenheim -- Elizabeth Peyton -- Germaine Richier -- Bridget Riley -- Pipilotti Rist -- Susan Rothenberg -- Niki de Saint Phalle -- Carolee Schneemann -- Cindy Sherman -- Kiki Smith -- Elaine Sturtevant -- Rosemarie Trockel -- Adreana Varejao -- Kara Walker -- Pae White -- Rachel Whiteread.
UCWS-2014-G-1779 donated by Prof. Eric Julian Manalastas
Keywords: Women artists -- Biography -- History and criticism; Art, Modern -- 20th century; Art, Modern -- 21st century